2008
DOI: 10.1037/a0012592
|View full text |Cite
|
Sign up to set email alerts
|

Motivational pathways to alcohol use and abuse among Black and White adolescents.

Abstract: Using data from a biracial community sample of adolescents, the present study examined trajectories of alcohol use and abuse over a 15-year period, from adolescence into young adulthood, as well as the extent to which these trajectories were differentially predicted by coping and enhancement motives for alcohol use among the 2 groups. Coping and enhancement motivations (M. L. Cooper, 1994) refer to the strategic use of alcohol to regulate negative and positive emotions, respectively. Results showed that Black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
135
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 92 publications
10
135
1
Order By: Relevance
“…Moreover, adolescents most often drink for social and enjoyment reasons [28,51], and one may assume that drinking to relieve emotional distress is relatively more prevalent among older and more experienced drinkers. Indeed, Cooper et al's [52] longitudinal study showed that selfmedication motives for drinking were reported gradually more often during the transition from adolescence into early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adolescents most often drink for social and enjoyment reasons [28,51], and one may assume that drinking to relieve emotional distress is relatively more prevalent among older and more experienced drinkers. Indeed, Cooper et al's [52] longitudinal study showed that selfmedication motives for drinking were reported gradually more often during the transition from adolescence into early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Last, we controlled for concurrent levels of individuals' motivation to drink to enhance positive emotions. Previous research has linked such motivation to drinking-related problems (e.g., Cooper et al, 2008), and analysis of the current data (Armeli et al, 2010) suggests a role of enhancement motivation in the link between negative affect and drinking level.…”
mentioning
confidence: 99%
“…[11][12][13][14] A couple of longitudinal studies have also shown that drinking motives predict changes in alcohol use over time, e.g., higher enhancement motives predict an increase in RSOD 15,16 and higher enhancement or coping motives predict an increase in alcohol-related problems. [17][18][19] The theoretical model of drinking motives assumes that they also depend on reinforcement achieved through feedback loops from past drinking, 8,9,20 i.e., the experience of positive effects of drinking in a group is likely to encourage further drinking for social motives.…”
Section: Introductionmentioning
confidence: 99%